2021
DOI: 10.1016/j.ijid.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Tracking COVID-19 with wastewater to understand asymptomatic transmission

Abstract: Introduction SARS-CoV-2 RNA is excreted in feces of most patients and therefore viral load in wastewater can be used as a surveillance tool to develop an early warning system to help and manage future pandemics. Methods We collected wastewater from 24 random locations at Bangkok city center and 26 nearby suburbs from July to December 2020. SARS-CoV-2 RNA copy numbers were measured using real-time polymerase chain reaction (PCR). Results SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
(23 reference statements)
1
28
0
Order By: Relevance
“…Since SARS–CoV–2 are excreted in the faeces of COVID-19 infected people, an increased emphasis should be laid on surveillance through wastewater-based epidemiology ( Nghiem et al, 2020 ) in order to predict upcoming waves or outbreaks of the virus ( Wannigama et al, 2021 ). Hence, developed as well as developing nations should use WBE tools for public health surveillance during and after the COVID-19 pandemic to gather epidemiological data and support suitable disinfection measures of the wastewater recycling process to make water useable.…”
Section: Sars-cov-2 Rna Detection Methods In Wastewater and Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since SARS–CoV–2 are excreted in the faeces of COVID-19 infected people, an increased emphasis should be laid on surveillance through wastewater-based epidemiology ( Nghiem et al, 2020 ) in order to predict upcoming waves or outbreaks of the virus ( Wannigama et al, 2021 ). Hence, developed as well as developing nations should use WBE tools for public health surveillance during and after the COVID-19 pandemic to gather epidemiological data and support suitable disinfection measures of the wastewater recycling process to make water useable.…”
Section: Sars-cov-2 Rna Detection Methods In Wastewater and Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
“…It means that a single person can discard billions of copies of SARS–CoV–2 RNA, thereby contaminating the wastewater ( Trottier et al, 2020 ). A recent study held at Bangkok Metropolitan and suburbs attempted to track the occurrence of COVID-19 in wastewater for understanding the asymptomatic transmission and exposed the increasing count of SARS–CoV–2 RNA in the wastewater in line with the growing number of COVID positive patients ( Wannigama et al, 2021 ). Additionally, the viral RNA has been found in the faeces of almost 15–83% SARS–CoV–2 infected patients ( Foladori et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teams from across the world have reported the presence of SARS-CoV-2 RNA in municipal wastewaters ( Ahmed et al, 2020 ; Fitzgerald et al, 2021 ; Giraud-Billoud et al, 2021 ; Haramoto et al, 2020 ; Kumar et al, 2020 ; La Rosa et al, 2020 ; Medema et al, 2020 ; Miyani et al, 2021 ; Nemudryi et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020 ; Rusiñol et al, 2021 ; Sherchan et al, 2021 ; Westhaus et al, 2021 ; Wu et al, 2021 ; Wu et al, 2020a ; Wurtzer et al, 2020 ). These studies have shown that WBE is suitable for spatial and temporal monitoring of SARS-CoV-2 across diverse communities ( Kitajima et al, 2020 ), serves as a leading indicator correlating strongly with future diagnosed cases, hospitalizations and deaths ( Miyani et al, 2021 ; Zhu et al, 2021 ), predicts the burden of undiagnosed infections at the population level ( Bivins et al, 2020 ; Daughton, 2020 ; Nemudryi et al, 2020 ; Wannigama et al, 2021 ) and can play a key role in optimizing public health decision-making ( Daughton, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Normalization of SARS-CoV-2 RNA counts by various fecal markers such as crAssphage (Wilder et al, 2021) or pepper mild mottle virus (Graham et al, 2021;Wu et al, 2020) has been used to tune wastewater data for correlation with COVID-19 cases. These approaches reflect an assumption that SARS-CoV-2 RNA loading in domestic wastewater is primarily driven by fecal shedding of SARS-CoV-2 RNA (Ahmed et al, 2020a;Wannigama et al, 2021;Wolfe et al, 2021). However, a recent study reporting near-source monitoring of wastewater from primary and secondary schools raises the potential for other shedding routes to contribute to the SARS-CoV-2 RNA load in wastewater (Gutierrez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%